MAKING SENSE OF TRANSITIONAL ADMINISTRATIONS OVER KOSOVO AND IRAQ - Upadhyay, Santosh Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Kosovo, the United Nations itself adopted the role of transitional administrator and drew its mandate from the Security Council resolution where as in Iraq, an occupying authority was acting as transitional administrator drawing its mandate by disregarding the law of belligerent occupation as well as relying extensively on the Security Council resolution. Both these transitional administrations though belong to different international legal structures, yet they exhibit almost a similar pattern of politico-economic reconstruction. They seek to radically challenge the post-UN Charter notion of international engagement in any sovereign domestic order. This part of the paper summarily mentions some of the interventions made by these administrations in Kosovo and Iraq.